Association between Serum Magnesium Level with Acute Coronary Syndrome (ACS) in Diabetes Mellitus (DM) Patients - Wulansari, Ratih; Soelistijo, Soebagijo Adi; Lefi, Achmad (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2019)
Introduction: Until now, cardiovascular complications are still the highest cause of death and disability in DM patients. Hypomagnesemia in DM accelerate atherosclerosis and can cause instability and plaque rupture which can lead to acute coronary syndrome.Methods: Design of this study was observational analytic using a